EIF4G-driven translation initiation of downstream ORFs in mammalian cells. Issue 18 (17th September 2020) - Nobuta, Risa; Machida, Kodai; Sato, Misaki; Hashimoto, Satoshi; Toriumi, Yasuhito; Nakajima, Shizuka; Suto, Daiki; Imataka, Hiroaki; Inada, Toshifumi
Abstract: Comprehensive genome-wide analysis has revealed the presence of translational elements in the 3′ untranslated regions (UTRs) of human transcripts. However, the mechanisms by which translation is initiated in 3′ UTRs and the physiological function of their products remain unclear. This study showed that eIF4G drives the translation of various downstream open reading frames (dORFs) in 3′ UTRs. The 3′ UTR of GCH1, which encodes GTP cyclohydrolase 1, contains an internal ribosome entry site (IRES) that initiates the translation of dORFs. An in vitro reconstituted translation system showed that the IRES in the 3′ UTR of GCH1 required eIF4G and conventional translation initiation factors, except eIF4E, for AUG-initiated translation of dORFs. The 3′ UTR of GCH1 -mediated translation was resistant to the mTOR inhibitor Torin 1, which inhibits cap-dependent initiation by increasing eIF4E-unbound eIF4G. eIF4G was also required for the activity of various elements, including polyU and poliovirus type 2, a short element thought to recruit ribosomes by base-pairing with 18S rRNA. These findings indicate that eIF4G mediates translation initiation of various ORFs in mammalian cells, suggesting that the 3′ UTRs of mRNAs may encode various products.